Opercular Perivascular Space Mimicking a Space-Occupying Brain Lesion: A Short Case Series - Roberts Tumelkans; Cenk Eraslan; Arturs Balodis (Diagnostics, 2025)
A newly recognized fourth type of perivascular space has recently been described in the radiological literature. Despite its growing relevance, many radiologists are still unfamiliar with its imaging characteristics, often leading to misinterpretation as cystic neoplasms. Due to its potential for diagnostic confusion, further studies are necessary—particularly those incorporating high-quality imaging examples across various presentations—to facilitate accurate recognition and classification. Perivascular spaces (PVSs) of the brain are cystic, fluid-filled structures formed by the pia mater and located alongside cerebral blood vessels, particularly penetrating arterioles, venules, and capillaries. Under normal conditions, these spaces are small (typically <2 mm in diameter), but in rare instances, they may become markedly enlarged (>15 mm), exerting a mass effect on adjacent brain tissue. This newly identified fourth type of PVS is found in association with the M2 and M3 segments of the middle cerebral artery, typically within the anterior temporal lobe white matter. It may mimic low-grade cystic tumors on imaging due to its size and frequent presence of surrounding perifocal edema. We present two adult male patients with this rare PVS variant. The first patient, a 63-year-old, had a brain magnetic resonance imaging scan (MRI) that revealed a cystic lesion in the white matter of the right temporal lobe anterior pole, near the middle cerebral artery M2 segment, with perifocal vasogenic edema. The second patient, a 67-year-old, had a brain MRI that showed a cystic lesion in the white matter and subcortical region of the right temporal lobe anterior pole, with minimal surrounding gliosis or minimal edema. The cystic lesions in both patients remained unchanged over time on follow-up MRI. These cases illustrate the radiological complexity of this under-recognized entity and emphasize the importance of differential diagnosis to avoid unnecessary intervention.